2006
DOI: 10.1152/japplphysiol.00518.2006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sex and exercise duration on growth hormone secretion

Abstract: Previous research clearly indicates a linear relationship between exercise intensity and growth hormone (GH) release and that this relationship is influenced by sex. The present study examined the GH response to increasing exercise duration in young men and women. Fifteen healthy subjects (8 men and 7 women) completed three randomly assigned exercise sessions (30, 60, and 120 min) at 70% of peak oxygen consumption. Blood samples were collected every 10 min beginning 30 min before exercise, for a total of 240 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…Interestingly, these gender differences disappeared when endurance exercise was performed intermittently (23), and were diminished with age (22). In contrast, when exercise intensity remains constant, exercise duration significantly increases integrated GH concentration in male more than females (24). Only a single study examined the effect of 3 30-s sprints with 20-min rest between the sprints on GH secretion in active men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these gender differences disappeared when endurance exercise was performed intermittently (23), and were diminished with age (22). In contrast, when exercise intensity remains constant, exercise duration significantly increases integrated GH concentration in male more than females (24). Only a single study examined the effect of 3 30-s sprints with 20-min rest between the sprints on GH secretion in active men and women.…”
Section: Discussionmentioning
confidence: 99%
“…First, ventilated patients report less daytime sleepiness and more vitality (46), which may impact upon their level of physical activity and protect against the disease (47). In addition, physical activity augments GH axis activity in young and to a lesser extent in older persons (48,49). Thus, exercise-induced increases in GH axis activity may have additional beneficial effects on LBM.…”
Section: Discussionmentioning
confidence: 99%
“…Deconvolution analysis revealed that increased GH levels resulted from an increase in the mass of GH secreted per pulse, with no change in pulse frequency or the half-life of elimination. Later studies from the same laboratory demonstrated that GH secretion correlates positively with duration of exercise when intensity is constant (145), is augmented by (122) compared GH secretion at rest and during exercise in men and women matched for age and physical fitness and demonstrated that GH secretion rates under resting conditions were greater in women; but during exercise, although absolute GH secretion rates were also increased, the increment from baseline was similar in men and women and did not correlate with sex hormones. This finding was confirmed in a later study (123).…”
Section: A the Acute And Long-term Effects Of Exercise On The Gh/ Igmentioning
confidence: 99%
“…The neuroendocrine pathways through which GH secretion is regulated during exercise are complex and poorly understood, but there is evidence that adrenergic, cholinergic, and opioid pathways are involved (89). The magnitude of the GH response to exercise is influenced by age (118 -120), gender (121)(122)(123), body composition (124 -126), physical fitness (118,120,127,128), and the intensity (114, 127, 129 -133), nature (134 -142), and duration (130,(143)(144)(145) of exercise ( Table 4). The impact of these variables has been more clearly defined in a recent series of meticulously carried out studies using ultrasensitive chemiluminescence GH assays and deconvolution analysis of GH secretion.…”
Section: A the Acute And Long-term Effects Of Exercise On The Gh/ Igmentioning
confidence: 99%